2014
DOI: 10.1038/jp.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnant women of ethnic minority: a potential contributor to preeclampsia

Abstract: Pregnant women of ethnic minority had lower median vitamin D levels which may contribute to a potential risk for preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
0
18
0
3
Order By: Relevance
“…There is also evidence that vitamin D levels prior to delivery are associated with sPTB, 6164 that levels of GC in cervico-vaginal fluid may help predict sPTB 65,66 , and that vitamin D deficiency may contribute to racial disparities in birth outcomes 67,68 . Specifically, vitamin D deficiency may contribute to potential risk for preeclampsia among Hispanic and African American women 69 . The population-specific differentiation associated with the variant rs222016 is consistent with the differential evolution of the vitamin D system between populations—likely in response to different environments and associated changes in skin pigmentation 70,71 .…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence that vitamin D levels prior to delivery are associated with sPTB, 6164 that levels of GC in cervico-vaginal fluid may help predict sPTB 65,66 , and that vitamin D deficiency may contribute to racial disparities in birth outcomes 67,68 . Specifically, vitamin D deficiency may contribute to potential risk for preeclampsia among Hispanic and African American women 69 . The population-specific differentiation associated with the variant rs222016 is consistent with the differential evolution of the vitamin D system between populations—likely in response to different environments and associated changes in skin pigmentation 70,71 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study examined the evidence linking vitamin D deficiency in pregnancy to PET among different ethnic groups. Although prevalence of vitamin D deficiency differed significantly among African-Americans (72.3%), Hispanics (10.6%), and Caucasians (2.1%), there were no direct associations between low 25(OH)D levels and risk for PET among different ethnic groups [130]. While another recent study in UK indicated a greater prevalence of white British women developed GHT (12.0%) and PET (3.4%), compared to Pakistani women (the proportion of GHT and PET were 5.4 and 1.7%, respectively) [131].…”
Section: Pet and Gdm Among Ethnic Disparitiesmentioning
confidence: 90%
“…Further, the maternal vitamin D deficiency is important to this mother's subsequent health, as vitamin D deficiency has been associated with hypertension. 10,11 It is well known that above the latitude of 37° tremors in otherwise healthy newborns, has largely been regarded as a physiologic condition without the need for treatment. In this study, healthy Japanese neonates were checked for craniotabes at 5 to 7 days as part of routine discharge.…”
Section: Postnatal Visitsmentioning
confidence: 99%